Poor Managerial Factors Drive Employee Turnover Intention in Indonesian State Bank - Nawawi, Nasruddin; Utina, Dian Angriani; S, Wagiman; Tamsah, Hasmin; Yusriadi, Yusriadi (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Covid-19 pandemic that has hit the whole world is a heavy blow to the world today. Banking employees are among those affected by the pandemic. It takes a manager's expertise in managing an organization, especially banking, in a situation like today. There is a difference in empirical evidence showing that leadership plays a significant role in reducing employee turnover. Through this study, the difference in empirical evidence is expected to be resolved with a conceptual framework that assumes that only "balancing work and family life" can reduce "employee turnover intention" caused by leadership failure due to poor managerial factors. This study uses a quantitative approach with the analysis tool SEM-Amos version 23. The population in this study is 8,000 bank employees at Bank Rakyat Indonesia (BRI), as many as 6,000 people, and at the Bank Pembangunan Daerah (BPD) SULSELBAR as many as 2,000 people. The sample was taken using an accidental sampling technique, randomly from anyone willing to fill out an online questionnaire—a sampling target of at least 100 people who fill out early. Until the specified time limit (4 weeks), only 211 employees (123 employees of BRI central and as many as 88 employees of BPD SULSELBAR) filled out the questionnaire and were declared complete. This study shows that poor managerial factors substantially contribute to the emergence of the desire to leave the company, especially in the banking world. However, if the balancing of work and family life is considered, the influence of organizational factors will be minor. This study also shows that poor managerial factors cause work and family life balancing to be disrupted, but employee turnover intention is not too significant. They are also proven by the direct contribution of poor managerial factors to employee turnover intention, which is greater than the indirect effect through balancing work and family life. This study confirms that balancing work and family life is very large in reducing employee turnover intention. So, if you want to reduce employee turnover intention, balancing work and family life must be considered. This study also contributes to developing agency theory which shows the relationship between organizational factors (poor managerial) and employees. The primary key to this relationship is balancing work and family life which must be a concern in the banking world. From a managerial perspective, the contribution of this study can also be seen that leadership, especially the motivational function, is essential in the banking world, where the work is even more than 8 hours per day. The other most important thing is the attention to salary/income that is empirical evidence that can eliminate the desire of employees to leave the company. On the other hand, managers must be able to convince by providing a balance between work and the interests of their employees' families.